USM ESTABLISHES COOPERATION WITH UNSULBA - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 3 November 2016 Universiti Sains Malaysia (USM) has established links for cooperation with Universitas Sulawesi Barat (UNSULBA) in various areas of study which include the arts and sciences.